The role of microbiota in nonalcoholic fatty liver disease: mechanism of action and treatment strategy - Shen, Siwen; Liu, Yao; Wang, Nuoya; Huang, Zhenhe; Deng, Guifang (Frontiers in Microbiology, 2025)
Non-alcoholic fatty liver disease (NAFLD) is now the most prevalent chronic liver disease worldwide, ranging from simple hepatic steatosis to non-alcoholic steatohepatitis (NASH) and hepatocellular carcinoma. It poses a significant public health challenge. Growing evidence indicates that the gut microbiota plays a key role in the development and progression of NAFLD. Advances in sequencing technologies, microbiome and metabolomics have helped identify characteristic microbial patterns and microbial-derived metabolites associated with NAFLD. The gut-liver axis has emerged as a central pathway linking intestinal microbes to liver function. Microbiota-derived metabolites, such as short-chain fatty acids, bile acids (BAs), and trimethylamine N-oxide (TMAO), have dual roles in hepatic lipid accumulation, inflammation, and insulin resistance, providing new insight into NAFLD pathogenesis. This review summarizes the mechanisms by which disruptions in the gut-liver axis contribute to NAFLD progression. It also outlines the therapeutic effects and mechanisms of current probiotics, with particular emphasis on next-generation probiotics like Akkermansia muciniphila and the potential benefits of its inactivated forms. Furthermore, we explore the role of prebiotics, plant-derived compounds, and synthetic agents in modulating gut microbiota and liver health. The review highlights key associations between specific bacterial species, microbial metabolites, and NAFLD, offering a theoretical basis for microbiota-targeted precision interventions and new therapeutic directions.